Developmental and Hormonal Regulation of Direct Shoots and Roots Regeneration in Coccinia Indica L - Shekhawat, M.S; Ravindran, C.P; Manokari, M (International Journal of Natural Sciences Research, 2014)
Multiple shoots were induced from the nodal meristms in Coccinia indica L. in present study. Maximum number of shoots (4.7) per explant were observed on Murashige and Skoog (MS) medium supplemented with 2.5 mgl-1 6-Benzylaminopurine (BAP). The response of explants towards the use of kinetin (Kn) was not impressive (3.6 shoots per explant) as compared to BAP. Application of auxin (Indole-3 acetic acid, IAA) in the medium caused cullogenesis from the basal part of the explants. Shoots were multiplied (47.3 shoots per culture flask) on MS medium supplemented with 1.0 mgl-1 each of BAP and Kn. Long and healthy shoots (4-5 cm long) were rooted (8-9 roots per shoot) on agar-gelled half-strength MS medium supplemented with 2.0 mgl-1 Indole-3 butyric acid (IBA). None of the shoot produced roots in ex vitro experiments even after five weeks in green house. In vitro generated plantlets were hardened in the green house and transferred to the pots and finally to the field with 100% success.